Réponses

2013-04-25T19:08:06+02:00

a) 2+6=-7x

a) 8+7=x

a) 15=x

 

b)6-x=-2

b)6+2=x

b)8=x

 

c)x-3=8

c)x=8+3

c)x=11

 

d)x+0=13

d)x=13-9

d)x=4

 

e)x+5=-5

e)x=-5-5

e)x=-10

 

f)5-x=0

f)5-0=x

f)5=x

2013-04-25T19:16:20+02:00

méthode :

 

2x+6=-7   peut s'écrire  2x + 6 - 6 = -7 -6       l'égalité reste vraie en ajoutant - 6 aux 2 membres

de celle-ci

                                          2x + 0 = - 13

                                           x= -13/2

 

Pour b.....f    utilise la même méthode